Axiology of Monetary Attitudes of Ukrainian Youth under martial law - Virna, Zhanna P.; Marchuk, Rostyslav P. (REICST, 2024)
Personal transformational changes in the consciousness of student youth during martial law actualize the study of the axiology of their monetary attitudes. It is noted that the content of monetary attitudes during martial law acquires a special content in the behavioural patterns of consumption style and depends on the value orientations of modern students. A program of empirical research has been developed and Individually-oriented survey of students. On the basis of the analysis of correlation pleiades, four monetary-value triads have been allocated. The empirical explication of the psychological content of the monetary-value galaxy of students demonstrates a high level of their social adaptation due to pronounced prosocial attitudes and cooperative behaviour. It is stated that monetary-value psychocomplexes are a specific prognostic benchmark of human economic behavior. The obtained results can be used in the work of psychological services of higher educational institutions.